Double Photodiode Readout System for the Calorimeter of the HERD Experiment: Challenges and New Horizons in Technology for the Direct Detection of High-Energy Cosmic Rays - Pietro Betti; Oscar Adriani; Matias Antonelli; Yonglin Bai; Xiaohong Bai; Tianwei Bao; Eugenio Berti; Lorenzo Bonechi; Massimo Bongi; Valter Bonvicini; Sergio Bottai; Weiwei Cao; et al. (Instruments, 2024)
The HERD experiment is a future experiment for the direct detection of high-energy cosmic rays and is to be installed on the Chinese space station in 2027. The main objectives of HERD are the first direct measurement of the knee of the cosmic ray spectrum, the extension of electron+positron flux measurement up to tens of TeV, gamma ray astronomy, and the search for indirect signals of dark matter. The main component of the HERD detector is an innovative calorimeter composed of about 7500 LYSO scintillating crystals assembled in a spherical shape. Two independent readout systems of the LYSO scintillation light will be installed on each crystal: the wavelength-shifting fibers system developed by IHEP and the double photodiode readout system developed by INFN and CIEMAT. In order to measure protons in the cosmic ray knee region, we must be able to measure energy release of about 250 TeV in a single crystal. In addition, in order to calibrate the system, we need to measure typical releases of minimum ionizing particles that are about 30 MeV. Thus, the readout systems should have a dynamic range of about <semantics>107</semantics>. In this article, we analyze the development and the performance of the double photodiode readout system. In particular, we show the performance of a prototype readout by the double photodiode system for electromagnetic showers as measured during a beam test carried out at the CERN SPS in October 2021 with high-energy electron beams.